Modified ELISPOT: Modifications of the Elispot Assay for T Cell Monitoring in Cancer Vaccine Trials - Malyguine, Anatoli (Analyzing T Cell Responses, 2005)
The use of the IFN-γ ELISPOT assay to evaluate cellular immune responses has gained increasing popularity, especially as a surrogate measure for CTL responses. We developed and validated some modifications of the IFN-γ ELISPOT assay to optimize immunological monitoring of various cancer vaccine trials. Taking into consideration that the main mechanism of cell-mediated cytotoxicity is the release of cytolytic granules that contain, among others, cytolytic protein Granzyme B (GrB), we developed the GrB ELISPOT assay. Extensive studies demonstrated that the GrB ELISPOT assay is specific, accurately measures the rapid release of GrB, is more sensitive than the 51Cr-release assay, and that it may be successfully applied to measuring CTL precursory frequency in PBMC from cancer patients. Assuming that immunological assays that demonstrate recognition of native tumor cells (tumor-specific) may be more clinically relevant than assays that demonstrate recognition of tumor protein or peptide (antigen-specific), we developed and validated the Autologous Tumor IFN-γ ELISPOT assay using PBMC from idiotype vaccinated lymphoma patients as effectors and autologous B cell lymphoma tumor cells as targets. The precursor frequency of tumor-reactive T cells was significantly higher in the postvaccine PBMC, compared with prevaccine samples in all patients tested. Furthermore, the specificity of these T cells was established by the lack of reactivity against autologous normal B cells. These results demonstrate the feasibility of evaluating tumor-specific T cell responses when autologous, primary tumor cells are available as targets. Modifications of ELISPOT assay described in this chapter allow more comprehensive assessment of low frequency tumor-specific CTL and their specific effector functions and can provide valuable insight with regards to immune responses in cancer vaccine trials.